2016
DOI: 10.1186/s13052-016-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions on early functional gastrointestinal disorders

Abstract: BackgroundFunctional gastrointestinal disorders (FGIDs) are chronic or recurrent gastrointestinal symptoms without structural or biochemical abnormalities. FGIDs are multifactorial conditions with different pathophysiologic mechanisms including altered motility, visceral hyperalgesia, brain-gut disturbance, genetic, environmental and psychological factors.Although in most cases gastrointestinal symptoms are transient and with spontaneous resolution in infancy multiple dietary changes and pharmacological therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 59 publications
0
25
0
3
Order By: Relevance
“…A review published in 2016 concluded that there was some evidence to support pharmacological interventions for constipation and rectal dis‐impaction as the first‐line therapy 27. However, pharmacological therapy appears to offer no benefit for other FGIDs that occur early in life 28.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…A review published in 2016 concluded that there was some evidence to support pharmacological interventions for constipation and rectal dis‐impaction as the first‐line therapy 27. However, pharmacological therapy appears to offer no benefit for other FGIDs that occur early in life 28.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
“…Despite the lack of drug benefits, and the emphasis on parental and nutritional support in the guidelines, there is still widespread overuse of medical management in FGIDs such as regurgitation and infantile colic 26, 27, 29.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%
“…La duración del tratamiento será el tiempo necesario hasta corregir el problema; es decir, iniciar con dosis-respuesta y mensualmente disminuir el medicamento hasta retirarlo y lograr evacuaciones diarias, blandas y sin dolor. 28,29,34,41 Cólico ¿Cómo se define el cólico en niños?…”
Section: ¿Cuáles Son Las Principales Causas De Estreñimiento En Lactaunclassified
“…At least few interventions are known to alleviate excessive crying in colicky neonates, but with no evidence-based recommendations [22]. Historically, antispasmodic drugs, e.g., dicyclomine was found to counteract colicky behavior compared to placebo [23][24][25] but severe adverse effects, including coma [26], excluded the possibility to use the drugs in infants.…”
Section: Introductionmentioning
confidence: 99%